2003
DOI: 10.1080/10253890310001605376
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Infection and its Impact on the HPA Axis, Cytokines, and Cognition

Abstract: Immediately after infection, Human immunodeficiency virus, type 1 (HIV-1) enters the central nervous system (CNS) and is localized in highest concentration in the hippocampus and basal ganglia. Since these areas are associated with HPA axis and autonomic activities as well as cognition, it has been hypothesized that these functions will be impacted adversely in HIV-1 infection. In the treatment of HIV infection, although the highly potent antiretroviral (HAART) drugs have been effective in reducing peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Previous investigations have demonstrated cause and effect relationships between production of HIV-1 proteins gp120 and Tat, and neuronal damage [17,19,21]. Consistent with these findings clinical reports detail correlations between HIV-1 proteins, IFN-γ, and neuron cell loss resulting in cognitive decline in HAD patients [14,19,23].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Previous investigations have demonstrated cause and effect relationships between production of HIV-1 proteins gp120 and Tat, and neuronal damage [17,19,21]. Consistent with these findings clinical reports detail correlations between HIV-1 proteins, IFN-γ, and neuron cell loss resulting in cognitive decline in HAD patients [14,19,23].…”
Section: Discussionsupporting
confidence: 72%
“…Later in the symptomatic phase of HAD, usually coinciding with CD4+ T-cell depletion to levels lower than 200 cells/mm 3 , the virus is sustained in the CNS primarily by resident microglia and macrophages that have invaded from peripheral tissues. These cells seemingly serve as both viral factories and as mediators for inflammatory events resulting in neuropathology and subsequent neuropsychiatric impairment; the sequelae of HAD linked to "AIDS dementia-associated neuron damage" [1,14,23,31]. Indeed, pathologic CNS immune dysfunction has been widely explored in many past studies of microglia; the primary host cells for HIV-1 in the CNS [8,13,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, on the basis of various reports, we proposed that changes in HPA axis activity may be a consequence of molecular mimicry between the HIV-1 genome and key control elements of the HPA axis [1] . For instance, it has been reported that the corticotrophin releasing hormone (CRH) response element binding protein (REB) binds to a specific region of the POMC promoter with sequence CTGTGCGCGCAG.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent reports suggest that changes in HPA axis regulation may be a consequence of molecular mimicry in the HIV virus genome and the key control elements of the HPA axis [12,13] . For instance, viral proteins gag and Ltr regions may interact with the pro-opiomelanocortin (POMC) promoter normally regulated by corticotrophin releasing hormone (CRH) [14,15] .…”
Section: Introductionmentioning
confidence: 99%